A tradução de expressões idiomáticas de baixa dedutibilidade metafórica: contribuições aos estudos fraseológicos bilíngues - Valença, Eloísa Moriel [UNESP] (Universidade Estadual Paulista (Unesp), 2016)
Taking into account the metaphorical variations of idiomatic expressions as well as the notion of correspondence proposed by the translation theories, this study aims to examine Italian Idiomatic Expressions of Metaphorical Low-Deductible (EIBDM), from the point of view of the Brazilian learner / translator, whose search for translational correspondences is a challenge. By EIBDM, we mean those combinatorial expressions in foreign language which presents, in its constitution, cultural metaphors difficult to understand in the target language because it contains historical, geographical, religious, mythological, weather (temporal) or simply linguistic elements, explicit or implicit, that are typical or significant only in the source language or in the native language (in our case, the Italian). It is a multidisciplinary research, guided by the theoretical frameworks regarding Lexicography and Phraseography (PORTO DAPENA, 2002; OLIMPIO DE OLIVEIRA E SILVA, 2007), Phraseology, Idiomatic Expressions and Culturemes (ZULUAGA, 1997; ORTÍZ ALVAREZ, 1997, 2000; CORPAS PASTOR, 1996; XATARA, 1995, 1998; PAMIES BERTRÁN 2007, 2008; MOLINA MARTINEZ, 2001), Metaphor and Metonymy (LAKOFF AND JOHNSON, 2002; KÖVECSES 2002, 2005, 2010) as well as Translation Studies (FELBER, 1984; BAKER, 1992) to support this research. The corpus of this investigation was selected from special dictionaries of IEs; the methodology was based on the use of the web as a corpus and on the establishment of the frequency of occurrence of Italian IEs.72 EIBDM were selected and classified typologically. Then an analysis of their metaphors was carried out, translational correspondences were proposed and a discussion of the underlying cultural aspects were presented. Furthermore, a dictionary model of this phraseological units was designed, for learners, teachers and translators of the Italian language. On that basis, this research sought to outline the path to be followed and the challenges to be faced in translating these phraseologisms, in order to provide theoretical and practical background to phraseological bilingual studies.

Levando em consideração as variações metafóricas presentes em expressões idiomáticas, bem como a noção de correspondência proposta por teorias da tradução, este trabalho analisou Expressões Idiomáticas italianas de Baixa Dedutibilidade Metafórica (EIBDM), do ponto de vista do aprendiz/tradutor brasileiro, cuja busca por correspondentes tradutórios representa um desafio. Por EIBDM entendem-se aquelas combinatórias da língua estrangeira que apresentam, em sua constituição, metáforas culturais de difícil compreensão, na língua alvo, por conter elementos históricos, geográficos, religiosos, mitológicos, meteorológicos (temporais) ou simplesmente linguísticos, explícitos ou implícitos, que são típicos ou significativos apenas na língua fonte ou língua de origem (no nosso caso, o italiano). Por se tratar de uma pesquisa multidisciplinar, partiu-se de teorias referentes à Lexicografia e Fraseografia (OLÍMPIO DE OLIVEIRA E SILVA, 2007), Fraseologismos, Expressões Idiomáticas e Culturemas (ZULUAGA, 1997; ORTÍZ ALVAREZ, 1997, 2000; XATARA, 1995, 1998; PAMIES BERTRÁN 2007, 2008; MOLINA MARTINEZ, 2001), Metáfora e Metonímia (LAKOFF E JOHNSON, 2002; KÖVECSES 2002, 2005, 2010), bem como correspondências tradutórias (FELBER, 1984; BAKER, 1992) para embasar esta investigação. O corpus da pesquisa foi selecionado em dicionários especiais de EIs e a metodologia pautou-se na utilização da web como corpus e no estabelecimento do limiar de frequência para as EIs italianas. Foram selecionadas e classificadas tipologicamente 72 EIBDM. Em seguida, foram feitas a análise de suas metáforas, as propostas de correspondências tradutórias, a discussão sobre os aspectos culturais subjacentes e a proposta de elaboração de um dicionário de EIBDM cujo público-alvo é aprendizes, professores e tradutores da língua italiana. Com isso, buscou-se delinear o percurso a ser seguido e os desafios a serem enfrentados na tradução desses fraseologismos, com vistas a fornecer subsídios teóricos e práticos aos estudos fraseológicos bilíngues.
The translation of idiomatic expressions of metaphorical low-deductible: contributions to phraseological bilingual studies
Keywords: Idiomatic expressions; Idiomatic expressions of metaphorical low-deductible; Bilingual phraseography; Metaphor; Dictionary of idiomatic expressions; Expressões idiomáticas; Expressões idiomáticas de baixa dedutibilidade metafórica; Fraseografia bilíngue; Metáfora; Dicionário de expressões idiomáticas